Implementasi Metode Simple Additive Weighting (SAW) Dalam Mendukung Keputusan Calon Penerima Beasiswa Pada MTS Nurul Ula - Ervina Febrianti; Erba Lutfina; Galuh Wilujeng Saraswati; Wildan Mahmud (Fakultas Sains dan Teknologi, Universitas Nasional Karangturi, 2025)
Scholarships are a form of educational aid to support students’ academic pursuits, especially for those with outstanding performance or financial constraints. However, the scholarship recipient selection process at MTS Nurul 'Ula is still conducted manually, which often results in inefficiency and a lack of objective assessment standards. This manual process leads to subjective evaluations, takes a considerable amount of time, and may result in inaccurate scholarship decisions. Therefore, this study aims to develop a Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to improve efficiency, accuracy, and transparency in the scholarship selection process. The SAW method was chosen because it allows for clear weighting of each selection criterion, such as academic grades, attitude scores, parental income, number of dependents, and extracurricular achievements. With this system, the selection process can be carried out more objectively based on structured mathematical weighting and calculations. The system is developed using the Delphi and MySQL database, following the Waterfall development model. The results of the study show that the implementation of the SAW-based DSS can accelerate the selection process, reduce subjectivity, and ensure that scholarships are awarded to students who meet the predetermined criteria. Thus, the system is expected to be a fairer, more accurate, and more efficient solution for supporting scholarship selection decisions at MTS Nurul 'Ula. Based on the results of the SAW calculations, an accuracy rate of 85% was achieved, indicating that the system provides accurate and reliable results in determining scholarship recipients.